New POLITICAL realities in the development of non-profit organizations in Russia - Elena Vyacheslavovna Galkina (Вестник Северо-Кавказского федерального университета, 2022)
Deals with non-profit organizations of civil society and political activity associated with the construction of the dialogue relations with the state power. New trends are seen in tougher laws for non-profit organizations and, therefore, concern the government in ensuring the national security of Russia.